Adaptation and inertia in dynamic environments. (13th September 2015) - Stieglitz, Nils; Knudsen, Thorbjørn; Becker, Markus C.
Abstract : Research summary : We address conflicting claims and mixed empirical findings about adaptation as a response to increased environmental dynamism. We disentangle distinct dimensions of environmental dynamism—the direction, magnitude, and frequency of change—and identify how selection shapes adaptive responses to these dimensions. Our results show how frequent directional changes undermine the value of exploration and decisively shift performance advantages to inert organizations that restrict exploration. In contrast, increased environmental variance rewards exploration. Our results also show that, in dynamic environments, the best‐performing organizations are generally more inert than less successful organizations. Managerial summary : Our research helps managers to understand under what business conditions investments into exploration and strategic flexibility are more likely to pay off. Dynamic business environments characterized by persistent trends and by large, infrequently occurring structural shocks reward strategic pursuit of temporary advantage. Thus, exploration and strategic flexibility are preferred strategies. In contrast, the challenge in frequently changing environments with fleeting opportunities is to identify and to focus on strategic actions whose payoffs on average are high, independent of environmental volatility. Low levels of exploration and long‐term strategic focus are preferred strategies in these circumstances. Copyright © 2015 John Wiley & Sons, Ltd.